Konflik Agama di Indonesia Problem dan Solusi Pemecahannya - Firdaus M Yunus (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
The perspective of religion by placing religion as a source of conflict has led to various attempts to reinterpret and then find common ground at a certain level with the hope to reduce conflicts among religious communities if there is mutual tolerance. On the exoteric level, religions are different, but on the esoteric level, religions are not similar. All religions are viewed as equally valid paths to God. However, in many ways, the reality shows that the tension between the religious communities is closely related to factors that are beyond the scope of religion. This is an important matter for all religious believers to keep the peace among them.